2022
DOI: 10.3390/su14053050
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Relationships between the Tourism-Transportation-Ecological Environment System of Provinces along the ‘Silk Road Economic Belt’ in China

Abstract: Taking nine provinces and cities along the ‘Silk Road Economic Belt’ as an example, this paper constructs an evaluation index system of the coupling coordination degree of the tourism–transportation–ecological environment system (TTE system), analyzes the spatial–temporal evolution and regional differences of the coupling coordination level of the TTE system from 2004 to 2016 using the mean square error index model and the scissor difference model, and uses the EKC curve model to further verify the interactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The conclusions drawn from the research on economy, transportation and coupling coordination degree all show a common feature: the B&R has a promoting effect on the comprehensive development of the regions along the route. This has also been mentioned in previous studies, such as studies that have concluded that the transportation and tourism industries in the areas related to the Silk Road Economic Belt are on the rise [23]. The difference is that this paper focuses on analyzing the coupling coordination degree of economy and traffic along the New Eurasian Continental Bridge, which is innovative compared to related research, and the conclusions drawn also have certain reference value for future research.…”
Section: Discussionmentioning
confidence: 75%
“…The conclusions drawn from the research on economy, transportation and coupling coordination degree all show a common feature: the B&R has a promoting effect on the comprehensive development of the regions along the route. This has also been mentioned in previous studies, such as studies that have concluded that the transportation and tourism industries in the areas related to the Silk Road Economic Belt are on the rise [23]. The difference is that this paper focuses on analyzing the coupling coordination degree of economy and traffic along the New Eurasian Continental Bridge, which is innovative compared to related research, and the conclusions drawn also have certain reference value for future research.…”
Section: Discussionmentioning
confidence: 75%
“…The hitherto analysis of the literature on urbanisation has shown that, despite numerous themes addressed there, it is possible to single out studies that focus on two cause-and-effect relations, i.e., the relation between progressing urbanisation and economic growth [45][46][47][48], and the one between progressing urbanisation and transport infrastructure [49][50][51][52] (transport [50,[53][54][55][56]). They contribute to the further exploration of research directions.…”
Section: Characteristics Of Urbanisationmentioning
confidence: 99%
“…Environmental resources, including energy, determine the development of the economy and its sectors: transport and tourism [54]. In the framework of sustainable development, the relationship between tourism and transport is particularly emphasised [9,54]. The COVID-19 pandemic, which ran from March 2020 to May 2022, altered travel patterns and cut tourism demand dramatically.…”
Section: Factors Of Energy Intensity Of Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on the spatial coupling of tourism development are from Chinese researchers, mainly due to China's collaborative development strategy. Research has focused on the coupling and synergy between transportation [34], ecology [35], urbanization [36] and tourism development; meanwhile, a few scholars have also paid attention to the coupling degree between the inbound tourism market and the environment [37] and export trade [38]. The research methods mostly include the coupling coordination model and coupling correlation model.…”
Section: Literature Reviewmentioning
confidence: 99%